Challenges and opportunities of genome edited crops: An analysis of experts' views in Italy through a Delphi survey - Annalisa Zezza; Marco Vassallo (Italian Review of Agricultural Economics (REA), 2024)
New Breeding Techniques (NBTs) in agriculture have generated significant interest due to their potential to address many sustainability challenges related to food production. However, this potential is hindered by existing regulations and negative societal attitudes. The debate is wide open internationally. In this study, a Delphi technique was applied to assess the potential challenges and opportunities associated with genome editing applied to Italian agriculture. To this extent, a panel ranging from 22 to 27 experts from different professions, including academics, staff scientists, policymakers and farmer associations has been interviewed. The Delphi process included two rounds of expert inputs to reach a reasonable consensus and, in some cases, a potential dissensus. Results revealed that experts reached a strong consensus on the potential benefits of NBTs in agriculture, such as greater agronomic performance and enhanced quality for consumers. Nevertheless, experts did not reach a consensus on excluding some potential risks, like possible toxicity or allergy generation. They also shared concerns about some socio-economic risks like limited seed access, traceability, or negative consumers' attitudes.
Keywords: Q16; O13; O33; 330; Delphi technique; innovation; New Breeding techniques; regulation; risk